KONSTRUKSI KETIDAKSETARAAN GENDER PADA REMAJA PEREMPUAN DI SMA NEGERI I KAWAY XVI (Studi Pasca Menonton Film Kartini 2017) - yana, rahmah husna (Universitas Teuku Umar, 2023)
This study aims to analyze how adolescent girls form an understanding of gender inequality after watching the film Kartini (2017). This film is positioned as an educational medium that can trigger critical reflection on the social constructs that limit the role of women. The research uses a descriptive qualitative approach with the social construction theories of Peter L. Berger and Thomas Luckmann, which includes three main stages: externalization, objectification, and internalization.The subjects of the study were students in class XII of Social Studies 1 and Social Studies 2 of SMA Negeri 1 Kaway XVI, who were selected purposively. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The results of the study show that Kartini's film is able to increase gender awareness in adolescent girls. At the externalization stage, female students began to voice their views on the gender role inequality that they experience on a daily basis. The objectification stage showed that their thinking was tested in social interactions, where some received support and some faced resistance from patriarchal culture. Meanwhile, at the internalization stage, social support has proven to be very influential on whether the values of equality can be truly accepted and appreciated.